Cross-Border Acquisitions, Multinationals and Wage Elasticities - Katariina Hakkala; Fredrik Heyman; Fredrik Sjöholm (Research Institute of Industrial Economics (IFN), 2007)
The growing number of cross-border acquisitions has in many countries raised concerns about labor demand consequences. In this study, we use detailed firm level data to examine how increased internationalization and multinational activity affect the volatility of employment, or rather, the wage elasticity of labor demand. We analyze whether the wage elasticity of labor demand differs between multinational and non-multinational firms as well as between foreign-owned and domestic firms, and we are able to distinguish between different skill groups of employees. Moreover, we separate between an acquisition effect and a general ownership effect. Our results do not show any general difference in wage elasticities between different types of firms.
Keywords: F16; F21; F23; J23; 330; FDI; Cross-Border Acquisitions; Multinational Enterprises; Foreign Ownership; Labor Demand; Skill Groups; GMM; Multinationales Unternehmen; Übernahme; Arbeitsnachfrage; Qualifikation; Lohn; Elastizität; Schweden